O sintoma na fala: estudo sobre a construção de um conceito - Vieira, Mariana Passos (2022)
This work should be read as a study that puts into perspective the elaboration movements, consurnig the speech symptom, carried out in the scope of the so could language clinic - a reflection trend that is relatated to the effort of defining the notion witch is central to such a clinical field. in this dissertation, it’s originality is attributed to the commitment assumed by the above mentions clinical field. this work follows a path that illuminates the roots and development of the language clinic. it highlights, above all, the construction, as the title registers the notion of symptom in speech, a notion/concept that goes through successive elaborations throughout the 2000s and that gains a special contour when the subject and the other are involved in them. it seeks to clarify the reasons for the distance that separates speech-language pathology and language clinics, the issue of diagnosis is introduced to operate such a differentiation